Study of plant production modells with different intensity in winter wheat production - Hornok, Mária; Pepó, Péter (Acta Agraria Debreceniensis, 2008)
The effects of crop rotation, nutrient supply and plant protection technologies were examined on the yield of Mv PÁLMA winter wheat variety and on the most important diseases of ear and leaf. Our experiments were carried out on chernozem soil in the Hajdúság in 2006 and 2007, and three plant protection technologies (extensive, average, intensive) and three irrigation variations (without irrigation, irrigated with 50 mm, irrigated with 100 mm) were applied in different crop rotation systems. In the triculture crop rotation a higher rate of infection was observed than in the biculture crop rotation, because the vegetative growth was more expressed after pea and these microclimatic factors were favourable for the development of pathogens. In the triculture crop rotation (pea – wheat – maize) the powdery mildew, DTR and leaf rust of wheat were present in both examined years (powdery mildew 5-15%, DTR 14-42%, leaf rust 8-37% in cropyear 2005/2006, powdery mildew 12-32%, DTR 9-29%, leaf rust 8-26% in cropyear 2006/2007). Fusaria could be observed in 2006 (depending on the plant protection technologies and nutrient supply in the biculture 7-27% and in the triculture 5-19%). With higher amounts of fertilizers the rate of infection increased and reached its maximum at the highest dose of nutrient supply (N200 +PK). We observed the highest rate of infection by ear and leaf diseases in the case of the extensive technology, while this rate could be considerably reduced by the application of the intensive technology. Both in 2006 and 2007, yields were the highest at the N100-200+PK levels in the triculture after pea (6028-7939 kg ha-1 in cropyear 2006, 6578-8690 kg ha-1 in cropyear 2007 depending on plant protection technologies), and at the N150-200+PK levels in the biculture after maize (6096-7653 kg ha-1 in cropyear 2006, 4974-8123 kg ha-1 in cropyear 2007 depending on the plant protection technologies). The highest yield maximums were reached when pea was the forecrop. The yields on the experimental plots of the intensive plant protection technology was 224-2198 kg ha-1 higher (depending on the forecrop) compared to the plots where the extensive technology was used. The highest yield without irrigation was at the N150+PK both in biculture and triculture crop rotation. Among the irrigated variations Ö2 and Ö3 at N200+PK fertilisation resulted in the highest yield in the biculture crop rotation, while the N100+PK level in triculture system. In the biculture crop rotation the extra yield was 14-51% higher (575-1225 kg ha-1 depending on plant protection technology) when 50 mm water was irrigated, and 15-54% higher (778-2480 kg ha-1) if 100 mm irrigation was applied comparing to the non-irrigated versions. The yield was 7-17% higher (560-1086 kg ha-1) in the Ö2 irrigation variation, and 8-23% (691-1446 kg ha-1) higher in the Ö3 irrigation variation compared to Ö1 irrigation variation (non-irrigated). A correlation analysis was made to reveal the connection between the yield, the amount of fertilizers, the rate of infection, the plant protection technologies and the forecrops. Strong positive correlation (0.846) was found between year and fusaria infection. Strong positive correlation was observed between fertilization and powdery mildew infection (0.525), fertilization and DTR (0.528), fertilization and yield quantity (0.683). Lower correlation was found between fertilization and leaf rust infection (0.409), and forecrop and yield (0.472), recpectively. Negative correlation was calcutated between plant protection technologies and DTR (-0.611), and plant protection technologies and leaf rust (-0.649).